2023
DOI: 10.1021/acs.jmedchem.3c00697
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biophysical and Biological Studies of N-Phenylbenzamide Derivatives Targeting Kinetoplastid Parasites

J. Jonathan Nué-Martinez,
David Cisneros,
María del Valle Moreno-Blázquez
et al.

Abstract: The AT-rich mitochondrial DNA (kDNA) of trypanosomatid parasites is a target of DNA minor groove binders. We report the synthesis, antiprotozoal screening, and SAR studies of three series of analogues of the known antiprotozoal kDNA binder 2- ((4-(4-((4,5-Bis(2-aminoimidazolines) (1) and bis(2-aminobenzimidazoles) (2) showed micromolar range activity against Trypanosoma brucei, whereas bisarylimidamides (3) were submicromolar inhibitors of T. brucei, Trypanosoma cruzi, and Leishmania donovani. None of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 105 publications
(336 reference statements)
0
1
0
Order By: Relevance
“…Several literature reports indicate that diversely substituted benzimidazoles feature distinct pharmacological activity and have found applications in diverse therapeutic areas, such as cancer, inflammatory disorders, viral, bacterial, and parasitic infections. [24][25][26][27][28] Thus, starting from 10 we synthesized a small library of derivatives. Among the novel compounds, the homogeneous timeresolved fluorescence (HTRF) binding assay revealed that compound 17 is the most potent one in interrupting the PD-1/PD-L1 complex (IC 50 in the submicromolar range).…”
Section: Introductionmentioning
confidence: 99%
“…Several literature reports indicate that diversely substituted benzimidazoles feature distinct pharmacological activity and have found applications in diverse therapeutic areas, such as cancer, inflammatory disorders, viral, bacterial, and parasitic infections. [24][25][26][27][28] Thus, starting from 10 we synthesized a small library of derivatives. Among the novel compounds, the homogeneous timeresolved fluorescence (HTRF) binding assay revealed that compound 17 is the most potent one in interrupting the PD-1/PD-L1 complex (IC 50 in the submicromolar range).…”
Section: Introductionmentioning
confidence: 99%